THE INFLUENCE OF PROVIDING OHS (OCCUPATIONAL HEALTH AND SAFETY) MATERIALS AND ITS IMPLEMENTATION ON THE PERFORMANCE OF PT. ABCD EMPLOYEES - Syamsudin, Syamsudin; Dewi Puspaningtyas Faeni (Musytari : Neraca Manajemen, Akuntansi, dan Ekonomi, 2024)
This study aims to identify and analyze the impact of providing OHS (Occupational Health and Safety) materials and the implementation of OHS practices by the company on workers at PT. ABCD in the event of unforeseen incidents such as workplace accidents. The provision of OHS materials and their application to the performance of employees at PT. ABCD is a scientific literature review article within the scope of Human Resources. The method used is quantitative research with a case study strategy, gathering information through observations, and questionnaires distributed to staff, operators, and supervisors at PT. ABCD. The results of the study indicate that providing OHS materials significantly enhances employees' understanding of the importance of safety and health practices in the workplace. Moreover, the effective implementation of OHS schemes increases employees' awareness of potential hazards and methods to prevent them. These findings highlight the importance of providing OHS materials and implementing OHS practices as preventive measures in creating a safe and healthy work environment, as well as a means for employees to apply safety and health principles in their daily lives. The study demonstrates the further growth of OHS schemes in the workplace.